2014
DOI: 10.3389/fonc.2014.00008
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen Bounce Following Stereotactic Body Radiation Therapy for Prostate Cancer

Abstract: Introduction: Prostate-specific antigen (PSA) bounce after brachytherapy has been well-documented. This phenomenon has also been identified in patients undergoing stereotactic body radiation therapy (SBRT). While the parameters that predict PSA bounce have been extensively studied in prostate brachytherapy patients, this study is the first to analyze the clinical and pathologic predictors of PSA bounce in prostate SBRT patients.Materials and Methods: Our institution has maintained a prospective database of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…High prevalence of PSA bounce among younger patients was consistent with previous reports on SBRT [15,16] and brachytherapy [17]. The mechanisms underlying PSA bounce and its association with age have not been fully elucidated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…High prevalence of PSA bounce among younger patients was consistent with previous reports on SBRT [15,16] and brachytherapy [17]. The mechanisms underlying PSA bounce and its association with age have not been fully elucidated.…”
Section: Discussionsupporting
confidence: 83%
“…CIRT was initiated on day 0. PSA was measured at 1,2,3,6,9,12,15,18,21,24,30,36,42,48,54, and 60 months post-CIRT at Gunma University Hospital. PSA bounce was defined as an increase in PSA over a cutoff followed by a spontaneous decrease to or below the pre-bounce nadir [17].…”
Section: Psa Assessmentmentioning
confidence: 99%
“…McBride et al [5] found that the mean age of those who experienced a bounce was significantly younger than those who did not. Vu et al [21] reported that younger age was the only factor that predicted PSA bounce following SBRT for prostate cancer. Park et al [22] showed that only pretreatment PSA level was associated with increased risk of PSA bounce.…”
Section: Discussionmentioning
confidence: 99%
“…Vu et al . reported that younger age was the only factor that predicted PSA bounce following SBRT for prostate cancer . Park et al .…”
Section: Discussionmentioning
confidence: 99%